Extraedad escolar en niños, niñas y adolescentes - Gaviria Arias, Mariana; Osorio Vásquez, Johan Andrés; Ossa Knight, Daniela; Parodi Grajales, Daniela; Salazar Isaza, Valentina; Cortés Mendoza, Any Isabel; Betancur Moncada, Manuela; Rodríguez Yepes, María Daniela; Ortiz Gañan, Manuela; Isaza Martínez, Manuela; Puerta Múnera, Jessica; Londoño Gómez, María José; et al. (Universidad Católica Luis Amigó, 2026)
School over-age status refers to the discrepancy between a student’s age and the grade level in which they are currently enrolled. Multiple factors influence the disengagement of a child or adolescent from the educational system. The convergence of elements such as social or intra- urban violence, poverty conditions, family difficulties, or personal decisions made by the student can shape the reasons behind the emergence of this socio-educational phenomenon.